Dependence of the mechanical properties of rigid PU foam on density. (May 2022) - Shivakumar, Neerakallu Dasappa; Deb, Anindya
Density is an important parameter that influences the properties and performances of rigid polyurethane foam. In this study, a systematic engineering approach is presented for determining the effect of density on mechanical properties of rigid/crushable PU foam for design applications. To this end, several mechanical performance parameters, that is, mean load and strength, secant modulus, energy absorption efficiency and densification strain are at first identified for the PU foam. Foam samples of different densities are obtained by varying the amount of liquid polyol–isocyanate of a desired mixing ratio in a constant-volume cubical mould and letting the blow and gelation reactions progress to completion. By conducting compression tests on cubic specimens of foam obtained, it is shown that various mechanical parameters of interest increase monotonically with respect to density. An SEM-based study on the effect of density on foam microstructure has also been carried out.